Beyond Neoliberalism? Crisis and the Prospects for Progressive Alternatives - Cahill, Damien (New Political Science, 2011)
The onset of the current global economic crisis was hailed by many as signalling the demise of neoliberal hegemony. Two years on however, neoliberalism appears to be quite durable. Indeed, after a brief period of Keynesian-type responses, states, on the whole, have embraced neoliberal solutions to the fiscal problems generated by the crisis. Greece, for example, is now following an IMF programme of privatisation and cuts to social expenditure, while other European nations are pursuing austerity policies. In the USA, state and municipal governments are selling off public assets in response to mounting deficits. This paper explains the durability of neoliberalism and the opportunities and challenges it creates for non-neoliberal progressive policy agendas. Drawing upon Karl Polanyi's conceptual framework, this paper argues that neoliberalism is best understood as a historically specific process of state and economic restructuring that is socially embedded through three mechanisms: ideological norms, class relations, and institutional rules. This paper examines responses by states to the crises and concludes that, although the ideological legitimacy of neoliberalism has been somewhat weakened, there is little evidence to suggest that the three mechanisms, through which neoliberalism is socially embedded, have been significantly eroded. The implication for progressive politics is that, just as neoliberalism is socially embedded, so would a successful progressive non-neoliberal political programme need to be socially embedded: through the articulation of a coherent alternative ideology; through the mobilisation of social forces; and through the institutionalisation of non-neoliberal rules and norms within the apparatuses of the state.
Keywords: Keynesian economics; economic policy; global financial crisis, 2008-2009; neoliberalism; progressivism; social embeddedness

Toward a new countermovement: a framework for interpreting the contradictory interventions of migrant civil society organizations in urban labor markets - Martin, Nina (Environment & Planning A, 2011)
Low-wage migrant workers in the United States confront a perilous labor market, where wages are low, the risk of injury on the job is high, and the fear of apprehension by immigration authorities is widespread. There is increasing empirical evidence that civil society organizations are becoming involved in mediating labor-market problems, but work remains to be done in developing a robust theoretical conception of why such organizations are involved in this arena and how we might evaluate the impacts of their interventions. This paper presents a framework for interpreting the role of migrant civil society organizations as labor-market intermediaries, by extending Karl Polanyi's theory of the 'double movement' and more recent writing to neoliberalism and precarious work. On the basis of data collected from migrant nonprofit organizations in Chicago, I theorize migrant civil society organizations as part of the creation of a new countermovement that protects the interests of both workers and employers from the destructive nature of an unregulated labor market, as predicted by Polanyi. I catalogue organizations' responses to precarious work and create a generalizable framework for evaluating the contingent outcomes of their strategies. Organizations' work is interpreted as complex and sometimes contradictory: the potential to shield workers and advocate for progressive change is in constant tension with the neoliberal patterns of state and economic restructuring that such organizations can support.
Keywords: United States; civil society; immigrants; industrial mediation; labour market; migrant labor; migrant labour; neoliberalism; salaries, wages, etc.; societies, etc.

Embedded Markets: A Dialogue between F.A. Hayek and Karl Polanyi - Migone, Andrea (Review of Austrian Economics, 2011)
The recent economic crisis has once more underscored the close connection between markets and social life, thrusting this point at the centre of the analysis of economic and political activity and has once more asked the question of whether and how individuals are embedded in both. Here I argue that an analysis and partial reconciliation of the positions of F. A. Hayek and Karl Polanyi on the topic can help in this debate.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; capitalist systems; embedded markets; history of economic thought

The social economy of new rural reconstruction - Jia'en, Pan; Jie, Du (China Journal of Social Work, 2011)
This paper employs the concept of ‘social economy’ to reflect on the authors' experiences in rural reconstruction efforts in Mainland China, including work on peasant cooperatives and community-supported agriculture. In practice, the social and the economic can never be clearly separated. Economic problems, which may superficially appear to be independent, are in fact over-determined by all kinds of social and cultural factors, so a holistic perspective of ‘social economy’ is needed to re-embed the economic into its social context. Such a perspective can help expand the space of our practice and reflection thereon, in particular helping practitioners to understand the difficulties encountered in rural reconstruction.
Keywords: China; new rural reconstruction; perspective; social economy

KARL POLANYI'S METACRITIQUE OF THE LIBERAL CREED Reading Polanyi's Social Theory in Terms of Dialectical Critical Realism - Despain, Hans G. (Journal of Critical Realism, 2011)
This paper interprets Karl Polanyi through dialectical critical realism. The paper maintains that this interpretation offers Polanyi methodological coherence and philosophical support. It further provides dialectical critical realism with an exemplar of explanatory critique. It is argued that the social theory of Polanyi aims at the demystification of market-systems as they are theoretically constructed by both orthodox and heterodox accounts of capitalism. Dialectical critical realism is best capable of situating the theoretical accomplishment of Polanyi's historical and dialectical critiques of social being.
Keywords: capitalism; critical realism; economic theory; economics; explanatory critique; liberal creed; neoliberalism; ontology; social history; social theory

The Embedded Market and Ideology Critique - Johnson, Pauline (Critical Horizons, 2011)
The article examines the ideology critical potentials of the concept of the embedded market, made famous by philosopher and economic historian Karl Polanyi. It explores several readings of this concept and assesses their ability to revive critical powers of sociology. It discusses the book "The New Spirit of Capitalism," by Luc Boltanski and Eve Chiapello, as a specific take on such an idea. It also offers a re-examination of Polanyi's interpretations of the embedded markets thesis.
Keywords: Boltanski and Chiapello; embedded markets; ideology; neoliberalism; philosophers; philosophy; social theory; sociology

Work and Neoliberal Globalization: A Polanyian Synthesis - Bandelj, Nina; Shorette, Kristen; Sowers, Elizabeth (Sociology Compass, 2011)
This article reviews sociological research about economic globalization’s impact on work and labor in developed and developing countries since the 1980s. We find that this period of neoliberal globalization influences work because of intensified activities of multinational corporations (MNCs), financialization of the global economy, and amplified prominence of international organizations, some of which diffuse neoliberal policy scripts while others mobilize a transnational civil society. Research we review generally points to liabilities of neoliberal globalization for workers. To understand these findings, we apply Karl Polanyi’s concepts of fictitious commodities, the self-regulating market, and the double movement. We propose that, on the one hand, the activities of MNCs, international financial organizations, and many states exemplify pushes for institutional separation of economy and society in effort to institutionalize the idea of a self-regulating market at a global scale, which increases labor commodification and global inequalities. On the other hand, the activities of social movements, including unions and transnational actors that target globalization’s impact on work, constitute the counter movement at national and global levels resisting marketization and pushing for labor decommodification. The aftermath of the ongoing economic crisis will tell to what extent this countermovement will be successful in generating an alternative to neoliberal globalization, and more protections for workers.
Keywords: double movement; fictitious commodities; globalization; neoliberalism; self-regulating market

Polanyi and Post-neoliberalism in the Global South: Dilemmas of Re-embedding the Economy - Sandbrook, Richard (New Political Economy, 2011)
Although Karl Polanyi Studied a different epoch and focused on Europe, his ideas have inspired an outpouring of studies on contemporary problems and prospects in the neoliberal era. The bulk of these studies pertain to industrial countries or global economic issues. However, the human, environmental and financial impact of market deregulation is arguably more devastating in the ‘developing’ countries than in the core. A question thus arises: do Polanyi's reflections on progressive alternatives to liberalism clarify contemporary debates on development alternatives in the Global South? I contend that democratic socialism – Polanyi's preferred remedy to the ‘demolition’ of society and nature occasioned by market civilisation – is problematical in light of what we have learned from the twentieth century, but his framework for evaluating alternatives – featuring the re-embedding of economy in society – remains as powerful as ever, I support this argument with an exploration of socialism and social democracy – as well as community – based alternatives arising from ‘reciprocity’. Each possibility raises distinctive dilemmas, as an analysis of cases reveals.
Keywords: Global South; communitarianism; development alternatives; global south; globalisation; globalization; political economy; post-neoliberalism; social democracy; socialism

Embedding Markets in Temporal Structures: A Challenge to Economic Sociology and History - Eisenberg, Christiane (Die Einbettung von Märkten in temporalen Strukturen: Eine Herausforderung für Wirtschaftssoziologie und Geschichte., 2011)
The essay examines from a historian's point of view the approaches to the analysis of market exchange in new economic sociology and explores in which way sociology and history can cooperate in embedding markets in temporal structures. In a first step the author sharply criticises the favourable reception given to Karl Polanyi's work "The Great Transformation" in the field of new economic sociology. In particular she discusses the narrowing of research perspectives and its negative side effects on the sociology of markets. There then follows a second step: in order to find a linking point for interdisciplinary cooperation, beginning with the current state of historical research, the author makes several considerations on the significance of temporal structures and the time factor in general in analysing markets and market societies.
Keywords: Continental Europe; England; Great Britain; economic history; economic sociology; history - methodology; interdisciplinary approach to knowledge; interdisciplinary research; longue durée; market society; socioeconomics; time structures

Contracts in the English NHS: Market levers and social embeddedness - Hughes, David; Petsoulas, Christina; Allen, Pauline; Doheny, Shane; Vincent-Jones, Peter (Health Sociology Review, 2011)
This paper draws parallels between the market trend in the English NHS and Polanyi's (1957) The Great Transformation account of how the rise of markets provokes a self-protective counter-reaction that tries to re-embed economic relations in social relations. We report findings from a qualitative study of NHS contracting, which examines the recent move to harder-edged contracts with greater use of financial penalties and incentives. In practice, use of these techniques tended to be confined to nationally-mandated sections of the contract rather than emerging from local bilateral agreements, and when things went wrong the parties relied more on cooperative behaviour than on the provisions of the contract to find solutions. Making the current contracting system work depended more on existing relational networks than on the incentive structures created by recent 'marketisation' initiatives, but the inability of the market to evolve as expected has encouraged policy makers to publish plans for further radical reforms.
Keywords: England; English NHS; NHS reforms; competition (economics); contracting; contracting out; cooperativeness; decentralization in management; financing of research; government agencies; health sociology; incentives in industry; information storage & retrieval systems - medical care; institutional cooperation; interviewing; marketisation; meetings; methodology; national health services; negotiation; organizational effectiveness - evaluation; organizational structure; organizational change; pay for performance; purchaser/provider relations; qualitative research; research methodology; risk management in business; secondary analysis; social context; sociology; theory

Nature, Capital and Neighborhoods: 'Dispossession without Accumulation'? - Kappeler, Aaron; Bigger, Patrick (Antipode, 2011)
The ongoing economic crisis, which originated in the USA and has since spread rapidly to capital markets worldwide, is massive, complex, and many times contradictory. One could say the same for responses to the crisis as governments, firms and multi-national institutions struggle to grasp the full magnitude of the event. This article interrogates the key commodities involved-land, labor and money-and the always-uneasy relations between spaces of social reproduction and capital. Such ambivalence is critical to understanding how new economic realities are formed in light of retreating neoliberalism as markets become destabilized. The analysis provided suggests the commodities involved in the housing crisis are the basis for a countermovement against dispossession.
Keywords: MARX, Karl, 1818-1883; United States; capital market; capitalism; housing market; international business enterprises; labor; labour; mixed economy; neoliberalism; social aspects

The Commodification of Pollution and a Preemptive Double Movement in Environmental Governance: The Case of Water Quality Trading - Mariola, Matt J. (Organization & Environment, 2011)
The management of environmental pollution has traditionally been accomplished via the regulatory power of the state, but more recently the rise of a new, market-based form of governance has been observed. This article examines the sector of water quality trading, in which caps are placed on surface water pollution and polluters can purchase “offset credits” from farms or other polluters who are under their cap. Using a content analysis of program case studies and federal and state trading rules, the author analyzes this emergent form of environmental governance using an expanded Polanyian framework that he terms the preemptive double movement. Instead of the state reacting to the dangers of a new market form after the fact, here the state uses its existing authority to constrain the market so that further environmental damage does not result. The author describes eight specific regulatory mechanisms that illustrate this preemptive double movement at work.
Keywords: Polanyi; business & the environment; commodification; double movement; ecological impact; nutrient trading; pollution; water quality management; water quality trading

The Embedded Firm: Corporate Governance, Labor, and Finance Capitalism - Williams, Cynthia A.; Zumbansen, Peer (Cambridge University Press, 2011)
The globalization of capital markets since the 1980s has been accompanied by a vigorous debate over the convergence of corporate governance standards around the world towards the shareholder model. But even before the financial and economic crisis of 2008/2009, the dominance of the shareholder model was challenged with regard to persisting divergences and national differences in corporate law, labor law and industrial relations. This collection explores this debate at an important crossroads, echoing Karl Polanyi's famous observation in 1944 of the disembeddedness of the market from society. Drawing on pertinent insights from scholars, practitioners and regulators in corporate and labor law, securities regulation as well as economic sociology and management theory, the contributions shed important light on the empirical effects on the economy of the shift to shareholder primacy, in light of a comprehensive reconsideration of the global context, policy goals and regulatory forms which characterize market governance today.
Keywords: business & economics / management; corporate governance; disembeddedness; international law; political science / public policy / economic policy

Grounding Globalization: Labour in the Age of Insecurity - Webster, Edward; Lambert, Rob; Beziudenhout, Andries (John Wiley & Sons, 2011)
*Winner of the 2009 Distinguished Scholarly Monograph Prize, awarded by the American Sociological Association Labor and Labor Movements section* Claims have been made on the emergence of a new labour internationalism in response to the growing insecurity created by globalization. However, when persons face conditions of insecurity they often turn inwards. The book contains a warning and a sign of hope. Some workers become fatalistic, even xenophobic. Others are attempting to globalize their own struggles. Examines the claim that a new labour internationalism is emerging by grounding the book in evidence, rather than assertion Analyzes three distinct places – Orange, Australia; Changwon, South Korea; and Ezakheni, South Africa – and how they dealt with manufacturing plants undergoing restructuring Explores worker responses to rising levels of insecurity and examines preconditions for the emergence of counter-movements to such insecurities Highlights the significance of 'place' and 'scale', and demonstrates how the restructuring of multi-national corporations, and worker responses to this, connect the two concepts
Keywords: Polanyi problem; critique; globalization; internationalism; labour; science / earth sciences / geography

Karl Polanyi: The Limits of the Market - Barnes, Tom (Journal of Australian Political Economy, 2011)
The article reviews the book "Karl Polanyi: The Limits of the Market," by Gareth Dale.
Keywords: DALE, Gareth; KARL Polanyi: The Limits of the Market (Book); Polanyi, Karl, 1886-1964

Embedding Economic Relationships through Social Learning? The Limits of Patient and Public Involvement in Healthcare Governance in England - Vincent-Jones, Peter (Journal of Law & Society, 2011)
The strategy for NHS modernization in England is privileging individual choice over collective voice in the governance of healthcare. This paper explores the tension between economic and democratic strands in the current reform agenda, drawing on sociological conceptions of embeddedness and on theories of reflexive governance. Building on a Polanyian account of the disembedding effects of the increasing commercialization of health services, we consider the prospects for re-embedding economic relationships in this field. An analysis is provided of the limits of the present legal and regulatory framework of Patient and Public Involvement (PPI) in establishing the democratic and pragmatist conditions of social learning necessary for effective embedding. We show how the attainment of reflexive governance in the public interest is dependent on such conditions, and on the capacities of patients and the public to contribute to debate and deliberation in decision making, including on fundamental policy questions such as how services are provided and by whom.
Keywords: Great Britain; National Health Service; disembeddedness; embeddedness; medical care; public interest; social learning

Would You Barter with God? Why Holy Debts and Not Profane Markets Created Money - Semenova, Alla (American Journal of Economics and Sociology, 2011)
Attempting to revitalize the substantive approach to economics in the tradition of K. Polanyi, this paper revives the neglected substantive theory of money's origins by Bernhard Laum and thus disputes the formal approaches that see the origins of money in the context of trade. A wide range of evidence, from archeological to etymological, is utilized to demonstrate that relations between men and God, carried out through the intermediary of state-religious authorities, played a causal role in the genesis of the ox-unit of value and account, and, further, in the origins of money, and, subsequently, coinage. The substantive state-religious approach presented in this paper is also compared and contrasted to the Chartalist perspective on money's origins. It is concluded that the substantive approach presented in this paper differs from the more formal approaches (e.g., Metallism) because it does not rely upon a projection of modern institutions and habits of thought (e.g., a medium of exchange; monetary taxation) into ancient societies.
Keywords: ancient societies; money; substantive approach

The Polanyi-Stanfield Contribution: Reembedded Globalization - Brown, Doug (Forum for Social Economics, 2011)
This essay describes and interprets J. Ron Stanfield's analysis of Karl Polanyi. Stanfield has helped to clarify Polanyi's "double-movement" thesis by arguing that the double movement of self-regulating market forces and the protective response is essentially about freedom versus security. These insights provide an analysis that takes Polanyi into the twenty-first century by developing a theory of "reembedded globalization." This is not something that Polanyi experienced before his death in 1964. Corporate globalization and the escalation of free-market rhetoric have led to a new round of disembedding since the 1970s, and this is evident by both the top-down, corporate globalization of privatization, deregulation, and marketization, as well as, by the challenges to it from the "movement of movements" coalescing around the World Social Forum. The most conspicuous evidence of this neo-protective response and its challenge to corporate-driven market forces is that between the security needs of the world's globalization victims and the freedom of transnational corporations to make profits anywhere and in any way throughout the world. Understanding the clash in this way suggests that for humanity to save itself, it must struggle to reembed globalization and put security ahead of unbridled freedom. Reembedding globalization requires asserting democratic security ahead of the economic freedom of big business.
Keywords: MARX, Karl, 1818-1883; Marxian; Sraffian; capitalist systems; current heterodox approaches; globalization; history of economic thought; international economic order; political economy; reembedded; socialism

Lineages of Embeddedness: On the Antecedents and Successors of a Polanyian Concept - Dale, Gareth (American Journal of Economics & Sociology, 2011)
Since the 1980s, much debate has revolved around Karl Polanyi's concept of the 'dis/embedded economy,' generating some light and not a little heat. This paper looks at three reasons that account for part of the 'heat.' It begins by tracing the sources upon which Polanyi drew. They include Karl Marx, Ferdinand Tönnies, and Max Weber, along with anthropology of the inter-war period, and German and American Institutionalist economics. After exploring the differing ways in which these varying currents conceptualize the relationship between economy and society, I explore the different interpretations of what Polanyi means by embeddedness, and the different purposes to which contemporary economic sociologists have put the term. For some, he is held up as the originator of a line of sociological analysis that treats 'the economy' as a subsystem 'embedded in' a social system. In this reading the emphasis is upon the moral underpinnings of market behavior, in contrast to the naturalism of Ricardo, Malthus and their heirs. For others, his 'disembedding' thesis contains a more radical tale: of the market economy coming to dominate 'society,' bringing forth a sorcerer's apprentice world of untrammeled market forces that, although human creations, lie beyond conscious human control.
Keywords: MARX, Karl, 1818-1883; POLANYI, Karl, 1886-1964; TONNIES, Ferdinand, 1855-1936; WEBER, Max, 1864-1920; economic philosophy; economics; embeddedness; influence (psychology); intellectual life - history; socioeconomics

Redistribution in Aegean Palatial Societies Redistribution and the Political Economy: The Evolution of an Idea - Earle, Timothy (American Journal of Archaeology, 2011)
Whether the Bronze Age Aegean economies can be described as "redistributive" depends on how one defines the term. The concept of redistribution itself has undergone several decades of critical archaeological analysis, much of it stemming from my early work in Polynesia. I consider here how Polanyi's ideas about redistributive economies have been expanded since the 1970s. My review complements the article in this Forum by Nakassis et al. and the contribution by Haistead, who discusses why and how the concept of redistribution still matters in studies of the Minoans and Mycenaeans. To some degree, we all agree: chiefs, and later kings, who sought power in archaic societies did so through many highly variable, contingent, and changing means, all designed to support political-economic strategies based on multiple systems of finance. The Bronze Age Aegean societies provide excellent examples of this process, as demonstrated by the contributors to this Forum.
Keywords: Aegean civilization; Bronze age; chiefdoms; economic aspects; kings & rulers; metals; redistribution; wealth

Redistribution in Aegean Palatial Societies Redistribution in Aegean Palatial Societies: Terminology, Scale, and Significance - Halstead, Paul (American Journal of Archaeology, 2011)
Nakassis et al., in their contribution to this Forum, argue that the term "redistribution" has been used with a range of meanings in the context of the Aegean Bronze Age and so obscures rather than illuminates the emergence and functioning of political economies. They call for detailed empirical investigation rather than reliance on ambiguous idealized types. Lupack and Schon concur, arguing respectively that the palace shared control of the Mycenaean economy with sanctuaries and local communities and that centralized production of craft goods (an,d thus elite strategies of wealth finance) developed late at the palace of Pylos. Pullen finds little archaeological support for Renfrew's extrapolation of centralized redistribution to the Early Bronze Age, while Christakis uses evidence of storage to argue the same for Prepalatial Crete and to play down the scale and importance of elite redistribution in the Minoan palaces. The calls for circumspect use of the term "redistribution" and for detailed empirical investigation are applauded, although these five papers arguably do not all attack the same form of redistribution. This response argues that redistribution sensu Polanyi, Finley, and Killen (i.e., centrally administered movements of goods and services without equivalence of value) retains considerable heuristic value in investigation of both textual and archaeological evidence for Bronze Age political economies.
Keywords: Aegean civilization; Eleia (Greece); Greece; Mycenaean civilization; Pylos site (Eleia, Greece); archaelogy; bronze age; economics; redistribution

Economic Surplus, Social Reproduction, Nurturance and Love - O'Hara, Phillip Anthony (Forum for Social Economics, 2011)
This paper examines the contributions of James Ronald Stanfield to social and political economy. We start the analysis with Stanfield's contribution to institution building through his education of PhD students, building a graduate program in political economy, and through the associations of social and political economy. Then we go on to scrutinise his creative developments and applications of the notions of economic surplus and social reproduction. This is followed by his extensive work on Karl Polanyi and the disembedded economy. Finally we explore his path-breaking analysis of the great capitalist restoration, the nurturance gap and love. Stanfield was one of the greatest institutionalists and social economists of the last hundred years, and these four areas of energetic creativity are his prime achievements in the area.
Keywords: Marxian; Sraffian; current heterodox approaches: socialist; history of economic thought: individuals

Conceptualizing the Economic Role of the State: Laissez-Faire, Technocracy, and the Democratic Alternative - Sabeel Rahman, K (Polity, 2011)
This article contrasts three visions of political economy that appear in the writings of Keynes, Hayek, and Polanyi, and discusses their relevance to current debates over economic policy in the United States. Keynes proposed optimizing market practices through technocratic governance. In recent decades, this influential approach has proven vulnerable to the revival of Hayek's laissez-faire arguments. Polanyi, by contrast, introduced a framework that criticizes both laissez-faire conceptions and the technocratic approach pioneered by Keynes. Because of its emphasis on democratic participation, Polanyi's reasoning provides the building blocks for a new type of contemporary progressive politics.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; KEYNES, John Maynard, 1883-1946; United States; economic policy; free enterprise; government regulation; progressivism; the state

Some Social Economics Concepts for Future Research - Stanfield, James Ronald (Forum for Social Economics, 2011)
Under the guidance of a recrudescent nineteenth century ideology, the governance of the global economy has been profoundly altered in the past three decades; indeed, a veritable Great Capitalist Restoration has emerged. It is important to view the transitioning economies and emerging market economies as part of this massive shift in governance. The concept of economic surplus offers a useful perspective on the political economy of governance regimes. Karl Polanyi's post-Marxian view of lives and livelihood provides important insight into the nature of the Great Capitalist Restoration, its ideologically-driven impetus, and its eventual foundering on the shoals of instability, insecurity, inequality, and social and ecological unsustainability. The ineluctable crisis of the Great Capitalist Restoration provides another opportunity to construct a viable democratic economic future, one that avoids the pitfalls that brought down the corporate-welfare state, and offers more than inauthentic, joyless commodity consumption. To build the Road to this Future, we will need a powerful heterodox economic analysis of agency and governance, guided by a vision of an economy which is subordinate to the lives it provisions.
Keywords: Marxian; Sraffian; capitalist systems: political economy; current heterodox approaches: socialist; international economic order; social economy

Economic Anthropology - Hann, Chris; Hart, Keith (Polity, 2011)
This book is a new introduction to the history and practice of economic anthropology by two leading authors in the field. They show that anthropologists have contributed to understanding the three great questions of modern economic history: development, socialism and one-world capitalism. In doing so, they connect economic anthropology to its roots in Western philosophy, social theory and world history. Up to the Second World War anthropologists tried and failed to interest economists in their exotic findings. They then launched a vigorous debate over whether an approach taken from economics was appropriate to the study of non-industrial economies. Since the 1970s, they have developed a critique of capitalism based on studying it at home as well as abroad. The authors aim to rejuvenate economic anthropology as a humanistic project at a time when the global financial crisis has undermined confidence in free market economics. They argue for the continued relevance of predecessors such as Marcel Mauss and Karl Polanyi, while offering an incisive review of recent work in this field. Economic Anthropology is an excellent introduction for social science students at all levels, and it presents general readers with a challenging perspective on the world economy today.Selected by Choice as a 2013 Outstanding Academic Title
Keywords: cultural anthropology; economic anthropology; social anthropology; sociology - general

Understanding India’s New Political Economy: A Great Transformation? - Ruparelia, Sanjay; Reddy, Sanjay; Harriss, John; Corbridge, Stuart (Taylor & Francis, 2011)
A number of large-scale transformations have shaped the economy, polity and society of India over the past quarter century. This book provides a detailed account of three that are of particular importance: the advent of liberal economic reform, the ascendance of Hindu cultural nationalism, and the empowerment of historically subordinate classes through popular democratic mobilizations. Filling a gap in existing literature, the book goes beyond looking at the transformations in isolation, managing to: • Explain the empirical linkages between these three phenomena • Provide an account that integrates the insights of separate disciplinary perspectives • Explain their distinct but possibly related causes and the likely consequences of these central transformations taken together By seeking to explain the causal relationships between these central transformations through a coordinated conversation across different disciplines, the dynamics of India’s new political economy are captured. Chapters focus on the political, economic and social aspects of India in their current and historical context. The contributors use new empirical research to discuss how India’s multidimensional story of economic growth, social welfare and democratic deepening is likely to develop. This is an essential text for students and researchers of India's political economy and the growth economies of Asia.
Keywords: India; business & economics; ethnic studies

Does the human capital discourse promote or hinder the right to education? The case of girls, orphans and vulnerable children in Rwanda - Balsera, Maria Ron (Journal of International Development, 2011)
This paper studies the implications of considering education as a human right and examining it through the lens of the human capital discourse. It uses Polanyi's idea of decommodification, as discussed by Offe and Esping-Andersen, as well as Foucault's concept of governmentality, to analyse the changes that are taking place in the education sector in post-genocide Rwanda. It focuses on the consequences of the human capital discourse for girls, orphans, children with disabilities and Batwa in Rwanda. The paper concludes that although the human capital discourse has brought attention and resources to education, the situation has worsened for some marginalised groups leading to growing inequalities and discrimination. Copyright © 2011 John Wiley & Sons, Ltd.
Keywords: Rwanda; commodification; decommodification; human capital; neoliberal governmentality; right to education

The second great transformation: Towards a solidarity society - Brie, Michael; Klein, Dieter (International Critical Thought, 2011)
The double transition to a society based on unfettered capital valorisation, which attempts to legitimize itself by claiming to be a democratic society founded on human rights, can be defined as the first great transformation of the contemporary period. These bourgeois capitalist societies are now in a crisis of their reproduction, integration, rule and security. Three possible scenarios can be discerned: the first attempts to continue the present development (conventional world), the second, the formation of authoritarian fortresses in the centres within an ocean of insecurity and degradation, or, the third, a new transformation to a solidaristic social development. This transformation would begin in capitalism and at the same time point beyond it to a society whose most important goal is the development of free individuals through solidarity-based associations in the economy, in politics and in culture. Its basis would be a solidarity-based multi-sector economy and a participatory democracy. Although the totality of a new society cannot be anticipated, concrete entry projects for a new second transformation can be developed.
Keywords: capitalism; double transformation; socialism; solidarity economy

Karl Polanyi's Institutional Theory: Market Society and Its "Disembedded" Economy - Cangiani, Michele (Journal of Economic Issues, 2011)
A fundamental principle of Karl Polanyi's institutional outlook is that any economic system has to be considered as a whole and as a historically specific social organization. This principle implies a comparative method and a critique of conventional economics. Besides, the problem of the interrelation between the economic system and other aspects of social life cannot be avoided. On this basis, Polanyi points out the peculiar "economic" nature of the market-capitalist society and explains the institutional transformations characterizing its history. The opposition "embedded/disembedded," used by Polanyi to distinguish pre-modern economies from the market economy, has been widely adopted in recent times, particularly by economic sociologists, as a key for understanding current complex economic phenomena. However, the reference to Polanyi often presupposes a distorted interpretation of his theory, and a different kind of institutional approach.
Keywords: comparative economics; disembedded economy; economic policy; economic systems; embedded economy; institutional economics; institutional method

The moral economy of the Didache - Draper, Jonathan A. (Hervormde Teologiese Studies, 2011)
This article applies the model of the moral economy in the ancient world, as formulated by Karl Polanyi and applied by Halvor Moxnes, to the economic relations reflected in the Didache. The study partly confirms Aaron Milavec's contention that the instructions in the text would provide an 'economic safety net' for members of the community by putting in place a system of generalised reciprocity and redistribution, although Milavec's depiction of the community as an 'urban working class' movement is found to be anachronistic. The 'communion of the saints' is very much an economic system with aspects of resistance to the Roman imperial system. However, the moral economy of the Didache is seen to reflect a number of ambiguities, particularly in its adoption of the Christian Housetable ethic but also in its adoption of the patron client terminology in the dispute between prophets and teachers on the one side and bishops and deacons on the other.
Keywords: Bible; Bible - terminology; Bible - theology; Christian ethics; MILAVEC, Aaron; ambiguity; economic systems; moral economy; theology

Another ‘Great Transformation’ or Common Ruin? - Smart, Barry (Theory, Culture & Society, 2011)
In the aftermath of the 1930s Great Depression, and as the Second World War was drawing to a close, Karl Polanyi concluded a critical analysis of market capitalism on an optimistic — and with the benefit of hindsight we can add premature — note, remarking that the ‘primacy of society’ over the economic system had been ‘secured’. Eighty years later, amidst the unresolved turmoil of another comparable global capitalist economic crisis and accumulating signs of a growing environmental crisis, both a direct legacy of the operation of the ‘market economy’, the remedy advocated by governments and policy-makers is effectively a return to ‘business as usual’. Notwithstanding various manifestations of public expression of dissatisfaction with the consequences of global ‘free-market’ capitalism, which include increasing inequality, poverty, unemployment, depletion of scarce natural resources, environmental destruction, pollution and waste, the default policy setting remains to restore global economic growth, to generate further increases in production and cultivate ever-rising rates of consumption, even if the risk is ‘common ruin’. However, there are a number of realistic, progressive and radical alternatives proposed by critical analysts, including a political program for ‘de-growth’ , a reinvention of communism and detailed policy proposals outlining the measures necessary to promote a transition to a ‘post-capitalist’ society with a sustainable economy.
Keywords: BAUMAN, Zygmunt; Farewell to Growth (Book); First As Tragedy, Then As Farce (Book); LATOUCHE, Serge; Living on Borrowed Time: Conversations With Citlali Rovirosa-Madrazo (Book); ZIZEK, Slavoj, 1949-; capitalism; communist hypothesis; de-growth; degrowth; economic growth; environment; financial crisis; nonfiction; sustainability

The Big Picture: 2010 Presidential Address to the American Society of Criminology* - Rosenfeld, Richard (Criminology, 2011)
Microanalysis holds sway over macroanalysis in contemporary criminology. All of criminology would be better off if greater attention were devoted to the big picture—the relationship between crime and the interplay of institutions in the social systems of whole societies. Microlevel researchers often assume that the reduction of individual criminal propensities leads ipso facto to reductions in aggregate crime rates, but the implied connection is illusive, has not been demonstrated, and is belied by the macroanalysis of crime. The perspectives, methods, and data of macrocriminology also need to be developed, however, if they are to advance our understanding of crime at the level of social systems. Emile Durkheim, Talcott Parsons, Karl Polanyi, and C. Wright Mills have contributed essential building blocks for the study of the big picture of crime. Improvements in the quality and timeliness of aggregate crime data, finally, are necessary to bolster the policy relevance of macrocriminology.
Keywords: MILLS, C. Wright; PARSONS, Talcott; aggregate crime rates; macrocriminology; social institutions

Neoliberalism as a state-centric class project: The Italian case - Briziarelli, Marco (Continuum: Journal of Media & Cultural Studies, 2011)
This essay sheds light on the neoliberal aspects of the Italian political-economic system exemplified in the relationship between capital, state and media. The main argument is that the specific marriage between neoliberalism and neocorporatism that characterizes Italy reveals a distinctive characteristic of neoliberalism: a class project relying heavily on the state. As Polanyi has suggested through the concept of 'embeddedness', capitalism has consistently developed through the double movement of preaching the independence of the free market from the state and requiring the state's protectionist interventions. After describing this state-centric framework to interpret neoliberalism, in the second part of the paper, I consider the political-economic history of Italy's recent decades, paying particular attention to the media system. I will examine the 'communicative performance' of neoliberalism in Berlusconi's discourses and concrete political decisions taken in the name of neoliberalism. The articulated relationship between media and politics reveals the continuous attempts by the advocates of neoliberalism to seize the state, not to reduce its intervention but in fact to manipulate the market.
Keywords: Italy; economic indicators; essays; mass media audiences; neoliberalism; political economic analysis

Positivism and 'Functional Theory' in the Thought of Karl Polanyi, 1907-1922 - Dale, Gareth (Sociology Compass, 2011)
Karl Polanyi is the author of a modern social science classic, The Great Transformation, as well as a number of well-known and widely debated essays collected in Trade and Market in the Early Empires and Primitive, Archaic and Modern Economies. These texts were researched and written either during his second exile in 1930s Britain or in wartime or post-war North America. Not so well known, however, are his Hungarian writings from the 1910s. Until recently, very few of these had been republished or translated, although this is in the process of being rectified [: Karl Polanyi: The Hungarian Writings]. With reference to new translations of his Hungarian writings, to interviews with his daughter, Kari Polanyi-Levitt, as well as to biographical essays by György Litván, Évá Gábor, Endre Kiss, and Zoltán Horváth, this article explores his early influences, drawing attention in particular to his flirtation with and then violent reaction against philosophical materialism and 'objectivist' sociology, his appreciation of Ernst Mach's positivism, and his adherence to the 'functional theory' of contemporary Guild Socialism.
Keywords: positivism; religion; social sciences; socialism

The Market and Falling Fertility: Why Darwin Needs Help From Polanyi - Yea, Sanghan (World Futures: The Journal of General Evolution, 2011)
Darwin said all living things tend to multiply. However, nowadays, maintaining fertility rate below the replacement level of 2.1, human beings appear to have opted to let their population shrink. Perplexingly, it occurs while the environment seems to become more suitable for their survival. In solving this puzzle, we get a great help from Polanyi. We proved that people choose to have fewer babies and consequently, usher in depopulation, because by giving them the chance to assess all the expenses necessary for raising children, the market makes the cost clarified increasingly, while the economic benefit from rearing their off-spring remains obscure.
Keywords: DARWIN, Charles, 1809-1882; and memes; below replacement-level fertility; cultural transmission; demographic change; depopulation; exchange; futures research; general evolution; human fertility; markets; memes; reciprocity; redistribution

Crisis and renewal: the outlines of a twenty-first century new deal - Block, Fred (Socio-Economic Review, 2011)
Most analyses of the US financial crisis of 2007–2009 focus on the proximate causes. This article sees the crisis as a consequence of the decline of a long-term pattern of accumulation in the USA and seeks to outline the requirements for a new period of dynamic economic growth. Drawing on work done by the French Regulation theorists and the US analysts of Social Structures of Accumulation, the paper attempts to describe the types of institutional changes that would be needed to spark a new period of stable economic growth in the USA and in the rest of the world economy. The paper outlines what a green mass consumption economy might involve.
Keywords: United States; capitalism; capitalist systems; crises; economic change; economic reform; financial crisis; green economy; institutional change

NAFTA and Gatekeeper: A Theoretical Assessment of Border Enforcement in the Era of the Neoliberal State - Ackerman, Edwin (Berkeley Journal of Sociology, 2011)
The coexistence of border-enforcement policies such as Operation Gatekeeper and economic liberalization programs such as NAFTA is arguably paradoxical given the simultaneous push towards afree flow of products but curtailed flow of labor. This paper presents a critical review and reassement of existing accounts of neoliberal statehood to make sense of this apparent puzzle. While some have argued that the state is eroding under neoliberal globalization, a more sophisticated analysis has focused on how it has been transformed. David Harvey and LoIc Wacquant focus on the role of the repressive apparatus in upholding neoliberalism. Building on Harvey and Wacquant, and returning to Karl Polanyi, I emphasize the ways in which the state has tried to make use of a repressive apparatus as a claim to social protection a function that becomes necessary as the state advances liberalization. The coexistence of NAFTA and Gatekeeper should be not be understood as an anomaly but rather as an expected feature of contemporary statehood.
Keywords: North American Free Trade Agreement (NAFTA); United States; border security; finance; free trade; liberalization; neoliberalism; social protection

Food crises, food regimes and food movements: rumblings of reform or tides of transformation? - Holt Gimenez, Eric; Shattuck, Annie (Journal of Peasant Studies, 2011)
This article addresses the potential for food movements to bring about substantive changes to the current global food system. After describing the current corporate food regime, we apply Karl Polanyi's 'double-movement' thesis on capitalism to explain the regime's trends of neoliberalism and reform. Using the global food crisis as a point of departure, we introduce a comparative analytical framework for different political and social trends within the corporate food regime and global food movements, characterizing them as 'Neoliberal', 'Reformist', 'Progressive', and 'Radical', respectively, and describe each trend based on its discourse, model, and key actors, approach to the food crisis, and key documents. After a discussion of class, political permeability, and tensions within the food movements, we suggest that the current food crisis offers opportunities for strategic alliances between Progressive and Radical trends within the food movement. We conclude that while the food crisis has brought a retrenchment of neoliberalization and weak calls for reform, the worldwide growth of food movements directly and indirectly challenge the legitimacy and hegemony of the corporate food regime. Regime change will require sustained pressure from a strong global food movement, built on durable alliances between Progressive and Radical trends.
Keywords: corporate food regime; corporations; food movements; food prices; food security; food sovereignty; food supply; global food crisis; hunger; neoliberalism; peasant studies; right to food; social change; strategic alliances (business)

On the Nation-Specific Features of Modernization in Russia - Yadov, Vladimir (Social Sciences, 2011)
The article offers information on the features that contribute to the modernization in Russia. It discusses various value structure theories from various persons. It says that from the analysis of world survey statistics, Yevgeny Yasin concluded that Russians are more conservative compared to other western countries. Details regarding the mentality of Russian people are discussed including Russians' high score on cycloid scale and their tendency to fulfill their task at the last moment. Moreover, it says that Russia's activist theories, Karl Polanyi and Douglas North's path dependence theory, and the global world system theory as a new phase to human civilization's history are important features to the country's modernization.
Keywords: Russia; Russia - social conditions; YASIN, Yevgeny; economic development; modernization (social science); modernization theory; nation-state; national interest; social development theory

After Neoliberalism - Antonio, Robert J. (The Wiley-Blackwell Companion to Sociology, 2011)
This chapter contains sections titled: * Clashing Models of Capitalism: Hayek VS. Polanyi * Market Liberalism's Return: From the “Not Quite Golden Age” to the “Great U - Turn” * Hegemonic Neoliberalism: From Crest to Crisis to Emphatic Reassertion(?) * Capitalism at the Point of Inflection: Neoliberalism's Wake * Conclusion * References
Keywords: 2008 financial meltdown; HAYEK, Friedrich A. von (Friedrich August), 1899-1992; Hayek's and Polanyi's classic texts; New Deal; The Great U-Turn; ascendant neoliberalism; cutting edge issues; great recession; hegemonic culture; neoliberalism; neoliberalism's wake; self-regulating market

Polanyi on Markets, Democracy and the Crisis of Liberalism - Ebner, Alexander (The Beginnings of Scholarly Economic Journalism, 2011)
Karl Polanyi, who was born in 1886 in Vienna and died in 1964 in Pickering, Ontario remains a most influential theoretical figure in the social sciences, in particular stimulating both analytical and policy-related concerns that are related with the new institutionalism in economics, sociology and political science. Polanyian insights on the political economy of economic development from an institutional perspective have persistently shaped a variety of discourses that range from the theory of the welfare state to research in comparative economic systems and economic anthropology. Polanyi’s “Great Transformation” may be singled out as a key contribution to both the domains of economic sociology and political economy, as it addresses basic tensions between the developmental dynamics of the market economy and the institutional substance of political democracy (Block 2001).
Keywords: crisis of liberalism; early writings; methodology; methodology of the social sciences

Marketization, Social Protection, Emancipation: Toward a Neo-Polanyian Conception of Capitalist Crisis - Fraser, Nancy (Business as Usual: The Roots of the Global Financial Meltdown, 2011)
BOOK ABSTRACT: Situates the current crisis in the historical trajectory of the capitalist world-system, showing how the crisis was made possible not only by neoliberal financial reforms but by a massive turn away from manufacturing things of value towards seeking profit from financial exchange and credit. Much more basic than the result of a few financial traders cheating the system, this is a potential historical turning point. In original essays, the contributors establish why the system was ripe for crisis of the past, and yet why this meltdown was different. The volume concludes by asking whether as deep as the crisis is, it may contain seeds of a new global economy, what role the US will play, and whether China or other countries will rise to global leadership. Contributors include: Giovanni Arrighi, Gopal Balakrishnan, Manuel Castells, Daniel Chirot, Fernando Coronil, Nancy Fraser, James K. Galbraith, David Harvey, Caglar Keyder, Beverly J. Silver, and Immanuel Wallerstein. The three volumes can purchased individually or as a set. Business as Usual is the first part of a trilogy comprised of the first three books in the Possible Future series. Volume 1: Business as UsualVolume 2: The Deepening CrisisVolume 3: Aftermath The three volumes are linked by a common introduction and can be purchased individually or as a set.
Keywords: capitalism; emancipation; feminism; gender; welfare state

Karl Polanyi, Globalisation and the Potential of Law in Transnational Markets - Joerges, Christian; Falke, Josef (Hart, 2011)
The patterns and impact of globalization have become a common concern of all international jurists, sociologists, political scientists, and philosophers. Many have observed the erosion of the powers of nation states and the emergence of new transnational governance regimes, and seek to understand their internal dynamics, re-regulatory potential, and normative quality. Karl Polanyi's seminal book - The Great Transformation - is attracting new attention to such endeavors, mirroring a growing sensitivity to the social and economic risks of dis-embedding politics. Their re-construction by Polanyi - including his warning against a commodification of labor, land, and money - provide the trans-disciplinary reference point for the contributions to this book. Political economy, political theory, sociology, and political science inform this discussion of Polanyi's insights in the age of globalization. Further theoretical essays and case studies look at his 'false commodities': money, labor (and services), and land (and the environment). Jurists have hardly ever discussed Polanyi, and the law has not been taken very seriously among 'Polanyians.' It is nevertheless clear that economic stability and social protection are simply inconceivable without the visible hand of law. The legal discussion in this book's concluding chapters do not, and cannot, depart directly from such premises. The framework of their analyses is, instead, informed by current debates on the emergence of para-legal regimes, the fragmentation of international law, and the prospects of constitutional perspectives within which the rule of law and the notion of law-mediated legitimate governance are established. Polanyi's notion of the co-originality of dis-embedding moves and re-imbedding countermoves can, however, be usefully employed in the re-construction of the sociological background of the moves and tensions which jurists discern.
Keywords: conflict of laws; jurisprudence; law - commercial; political science - history and theory

Karl Polanyi and the New Economic Sociology: Notes on the Concept of (Dis)Embeddedness - Machado, Nuno Miguel Cardoso (Social Science Research Network, 2011)
Within the context of the New Economic Sociology, Karl Polanyi is almost universally considered the "father" of the concept of embeddedness. However, this concept has been subject to selective appropriation by this discipline and its relationship to the remaining theoretical edifice constructed by Polanyi has been neglected. It is, in fact, possible to refer to the "great transformation" to which the concept of embeddedness has been subjected: whereas in Polanyi’s work it is associated with the macro(economic) level and is used as evidence of the exceptional nature of the capitalist market economy –- disembedded from society –- in NES, it is normally associated with the meso (and even micro) level, on the assumption that all economies –- including capitalist economies -– are embedded. in RCCS Annual Review, No. 3, pp. 119-140
Keywords: Karl Polanyi; capitalism; embeddedness; market economy; new economic sociology

Whither the Counter-Movement? Hayek, Polanyi, and the Politics of No Alternative - Mudge, Stephanie (Conference Papers -- American Sociological Association, 2011)
This paper turns Karl Polanyi's concept of the "double movement" back on Polanyi and his intellectual contemporary, Friedrich Hayek, as a means to insight into the structural conditions of counter-movement in the second half of the 20th Century. After elaborating on the double movement concept, I contrast the trajectory of Polanyi and his greatest work, The Great Transformation, with that of Friedrich Hayek and his contemporaneous Road to Serfdom--treating each as protagonists in the movement/counter-movement system of relations that, for Polanyi, is the site of history's forward motion. Building on citation data, news articles, archival records and secondary sources, I argue that Polanyi's conditions of intellectual production--including a lack of economic allies in the capitalist West, professional instability, tenuous ties to academic economics, and a lifetime of financial insecurity--explain the ongoing quarantine of Transformation within the academic social sciences. These conditions of production contrast starkly with the Hayekian counterexample. Taken together, the analysis casts light on the ongoing hegemony of the "liberal creed" and the weakness of effective opposition: the trajectory of the two figures offers clues into how structures of intellectual production are linked to (or severed from) movement and counter-movement, offering insight into why, even in the face of financial crisis and significant public anger against the moneyed ranks of the financial sector, we continue to exist in a world of "no alternative".
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; POLANYI, Karl, 1886-1964; capitalism; intellectuals; protagonists (persons)

Karl Polanyi And The Great Transformation - Örmeci, Ozan (Sosyal Bilimler Dergisi, 2011)
Özet: 20. yüzyılın önde gelen iktisatçılarından olan Karl Polanyi (1886-1964), Büyük Dönüşüm adlı eserinde ortaya koyduğu özgün tezler ile halen kapitalizme en ciddi eleştiriyi getirmiş kişilerden biri kabul edilmektedir. Polanyi'nin klasik ENG: Karl Polanyi is known as one of the most famous economists of the world who strongly criticized liberalism and the idea of self-regulating market. Polanyi’s masterpiece The Great Transformation is still accepted as one of the most powerful critiques of liberal economics and many writers from different political backgrounds refer to this book while criticizing the dominant liberal economic understanding. The Great Transformation is a very rich and complex book in which Polanyi analyzes the evolution of the free-market ideology and the counter movement against the damages of liberal economics. Although Polanyi called himself as a socialist, his ideas are very dense and it is not easy to label him as a defender of certain ideology.
Keywords: Great Transformation, The (Book); review

Adventures of an Austrian Trio Abroad: The Influence of Schumpeter, Polanyi and Hayek in Turkey and the Dissemination of Their Work - Ozveren, Eyup (The Dissemination of Economic Ideas, 2011)
Keywords: Austrian; Keynesian; Keynesianism; evolutionary; general aggregative models: Keynes; history of economic thought; history of economic thought since 1925: historical; history of economic thought: individuals; institutional; post-Keynesian; role of economics; role of economists

Reading the Story of Law and Embeddesness through a Community Lens: A Polanyi-Meets-Cotterrell Economic Sociology of Law [article] - Perry-Kessaris, Amanda (Northern Ireland Legal Quarterly, 2011)
In this paper I propose that role of law in Karl Polanyi's concept of the 'always embedded economy' (Block 2003) can be enriched by the application of the lens of community (Perry-Kessaris 2008) developed by Roger Cotterrell (1996-present). I begin with Polanyi's suggestion that economic action and interaction are always 'embedded' in wider social life. Reading through the lens of community, we can be more specific: any actor is at once engaged, to different degrees (from fleeting to stable), in multiple types (whether focusing on instrumental, traditional, affective and/or belief-based action) of social life. I then explore a second, implicit, cornerstone of Polanyi's argument: that analytical and normative approaches to economy may become dis-embedded from wider social life. Reading through the lens of community we can again be more specific: In the transformation to a market society, the analytical and normative approaches that are central to economic actions and interactions are confused with, and privileged over, those that are central to non-economic actions and interactions. This confusion and privileging can have what we might call a performative effect on action and interaction. Finally, I explore Polanyi's story of law as a facilitator both of dis-embedding movements and of re-embedding counter-movements. The application of a law-and-community lens suggests some additional details of that storyline and that there are additional plotlines to be pursued. The practical potential of this Polanyi-meets-Cotterrell economic sociology of law is briefly illustrated with references to two 21st Century cautionary tales: the World Bank's investment climate programme and the 2008 financial crisis.
Keywords: COTTERRELL, Roger; United Kingdom; economic sociology of law; embeddedness; investment climate; law and community

Double Movements of Destruction and Regulation: Commodity Chains and a New Political Economy of the Environment - Roberts, J.; Carmin, JoAnn; Rudel, Thomas (Conference Papers -- American Sociological Association, 2011)
Sociologists have examined the ways in which capitalism contributes to environmental degradation as well as how, in selected circumstances, it increases efficiency while reducing pollution and human injustices. In this review, we draw on Polanyi's concept of the double movement to illustrate how self regulating markets give rise to environmental degradation and inequities and, in response, how these conditions often stimulate the emergence of collective action in pursuit of regulatory and social reforms. This process is iterative, with capitalist initiated degradation of the environment followed by regulatory reform and then efforts to weaken the regulatory regimes. We illustrate how resource extraction contributes to environmental degradation and power inequalities, pollution from industrial production is unequally distributed among workers and communities, and how the desire to limit exposure to risk has opened new markets and led to policies that contribute to consumption.
Keywords: capitalism; commodity chains; consumption (economics); double movement; environmental degradation; industries; pollution

Towards a Neo-Polanyian Political Economy of Development - Sandbrook, Richard (Conference Papers -- International Studies Association, 2011)
The Global South has entered an era of ideological flux. The inadequacies of neoliberalism have spawned a widespread questioning of this dominant worldview. Intellectuals and political movements search for an alternative development ideology that explains what has gone wrong, provides a vision of a more desirable future and suggests a process for achieving this goal. Responding to these challenges, the World Bank and other purveyors of the dominant model have undertaken a gradual shift from an unpopular and inefficacious “Washington Consensus” to a more complex and politically progressive “Post-Washington Consensus”. This shift, though blunting the attack on neoliberalism, has moved the debate on legitimate development strategies to the left and towards more statist approaches. Socialism, the developmental state, social democracy, and emancipatory community-based development have moved back into development discourse. In an earlier era of ideological flux, Karl Polanyi probed the origins of the implosion of economic liberalism in the Great Depression and two world wars, as well as the alternatives that might, by re-embedding the economy in society, allow people to live freer and more secure lives. These reflections came together in The Great Transformation, his masterwork that appeared in 1944. Although Polanyi studied a different era (1830-1940) and focused on Europe, his ideas have inspired an outpouring of studies on contemporary problems and prospects in the neoliberal era (since 1980). The bulk of these studies pertain to industrial countries or global economic issues. However, the human, environmental and financial impact of market deregulation is arguably more devastating in the ‘developing’ countries than in the core. A question thus arises: do Polanyi’s reflections on progressive alternatives to liberalism clarify contemporary debates on progressive alternatives to neoliberalism in the Global South?
Keywords: Global South; World Bank; economic development; global south; ideology; political movements; social democracy; socialism